Implicit motives and basic psychological needs. Issue 1 (8th October 2018) - Schüler, Julia; Baumann, Nicola; Chasiotis, Athanasios; Bender, Michael; Baum, Ingrid
Abstract: The present article starts with discussing similarities and differences between conceptualizations of human needs in self‐determination theory (SDT; Deci & Ryan [1985], Intrinsic motivation and self‐determination in human behavior ; Deci & Ryan [2000], Nebraska symposium on motivation: Perspectives on motivation ) and motive disposition theory (MDT; McClelland, Human motivation, 1985). The second section focuses on the two‐process model of psychological needs (Sheldon [2011], Psychological Review, 118: 552), which aims to integrate the two approaches, whereas the third section highlights some aspects of both theories that are still decoupled or even contradictory, but nevertheless still have a high potential to be linked. These three aspects are (a) the noncorresponding concepts of implicit power motive (MDT) and basic need for autonomy (SDT); (b) the differentiation of needs into hope and fear components, which is theoretically embedded in MDT, but not in SDT; and (c) MDT researchers' differentiation into an implicit and explicit motivational system, which is not included in SDT. Particularly, the last section highlights the potential for areas in which further integration is possible, which provides a foundation for comprehensive and exciting research on human motivation.